Coral reefs at Qiziwan National Marine Park in 2023: spatial variability and their relationship with environmental factors - Zhao, He; Zhang, Junling; Yang, Haijun; Li, Yiping; Liu, Xiangbo; Liu, Yicheng; Zhu, Wentao; Wang, Aimin; Li, Xiubao (Frontiers in Marine Science, 2024)
Introduction In 2023, a comprehensive survey was conducted at Qiziwan National Marine Park (QZW) to assess marine environmental variables, coral communities, and ecosystem parameters. This study aimed to evaluate the current state of coral ecosystems across different regions within the park. Methods The survey covered 19 sampling stations distributed among four regions: Xiaojiao Park, Zhongjiao Park, Dajiao Park, and Shayutang Village. Various marine environmental parameters were measured, and coral species were identified and recorded. Results A total of 67 species of reef-building corals belonging to 25 genera were identified. Dominant species included Porites lutea, Goniopora columna, Platygyra sinensis, Favites flexuosa, Galaxea fascicularis, and Acropora millepora. Coral coverage was found to be low at Xiaojiao Park, with high levels of turbidity and dissolved inorganic nitrogen, likely due to the nearby Changhua Port. Dajiao Park's sandy substrate made it unsuitable for coral survival. In contrast, Zhongjiao Park and Shayutang Village exhibited the best coral ecosystems. Redundancy analysis indicated that turbidity and substrate types were significant factors influencing coral distribution. Discussion The live coral coverage at Xiaojiao Park, parts of Zhongjiao Park, and Dajiao Park declined from 14.03% in 2017 to 11.73% in 2023. This decline is potentially attributed to frequent marine construction and land use changes. Anthropogenic disturbances appear to have worsened environmental conditions, undermining coral reef survival at QZW.